Preparation and characterization of yttrium barium copper oxide (YBCO) superconductorwith addition of cobalt oxide (C O 3 O 4 ) / Nor Erwana Yunus, Nur Jannah Azman and Nurul 'Ain Jamion - Yunus, Nor Erwana; Azman, Nur Jannah; Jamion, Nurul 'Ain (Universiti Teknologi MARA, Negeri Sembilan, 2018)
This study was carried out to investigate the electrical properties of YBCO sample as superconductor and the effect of addition of Co 3 O 4 on the superconducting properties of YBCO superconductor. The YBCO sample was prepared by solid state reaction route. The samples were prepared by each with weight percentage of cobalt oxide of x= 0.00, x= 0.01, x= 0.02 and x= 0.03. Electrical Conduction by Multimeter, Fourier Transform Infrared (FTIR), Critical temperature (T c ) measurement, X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) were conducted for analysis. Multimeter showed all samples were in electric conduction, FTIR showed that carbonyl compound in the sample was removed after calcinations. T c measurement showed that the critical temperature of sample of x= 0.02 was increased compared to sample of x= 0.00. XRD showed all samples have orthorhombic structure and SEM showed that the grain size was increased as increased the cobalt addition in YBCO superconductor. Besides, the EDX also showed the composition of elements YBCO were tally with chemicals used for pure YBCO and addition cobalt oxide into YBCO superconductor.